2011
DOI: 10.1038/ni.2180
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic blockade of PD-L1 and LAG-3 rapidly clears established blood-stage Plasmodium infection

Abstract: Plasmodium infection of erythrocytes induces clinical malaria. Parasite-specific CD4+ T cells correlate with reduced parasite burdens and severity of human malaria, and are required to control blood-stage infection in mice. However, the characteristics of CD4+ T cells that determine protection or parasite persistence remain unknown. Here we show that P. falciparum infection of humans increased expression of an inhibitory receptor (PD-1) associated with T cell dysfunction. In vivo blockade of PD-L1 and LAG-3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
499
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(537 citation statements)
references
References 51 publications
30
499
2
6
Order By: Relevance
“…To treat IFNg-deficient mice, antibodies were given three times 3 days apart. To deplete CD8 þ T cells, anti-CD8 (53.5.8, BioXcell) was given as described previously (22). Briefly, depleting antibody (100 mg) was administrated 1 day before anti-4-1BB/anti-PD-1 administration and every 5 days thereafter for a total of three doses.…”
Section: Immune-cell Phenotyping Using Flow Cytometrymentioning
confidence: 99%
“…To treat IFNg-deficient mice, antibodies were given three times 3 days apart. To deplete CD8 þ T cells, anti-CD8 (53.5.8, BioXcell) was given as described previously (22). Briefly, depleting antibody (100 mg) was administrated 1 day before anti-4-1BB/anti-PD-1 administration and every 5 days thereafter for a total of three doses.…”
Section: Immune-cell Phenotyping Using Flow Cytometrymentioning
confidence: 99%
“…In a murine transplantable tumor model, it was observed that PD-1 and LAG-3 were coexpressed on tumor-infiltrating CD4 + and CD8 + T cells (23). Plasmodium infection induced T cell exhaustion, which could be restored by the blockade of PD ligand 1 (PD-L1) and LAG-3 in vivo; blocking PD-L1 and LAG-3 restored CD4 + T cell function, amplified the numbers of follicular helper T cells, enhanced protective Abs, and rapidly cleared the established bloodstage Plasmodium infection in mice (25). LAG-3 also defines an active CD4 + CD25 high Foxp3 + regulatory T cell subset, the fre-quency of which is enhanced in the PBMCs of cancer patients (26).…”
mentioning
confidence: 99%
“…Following 3 weeks of infection, mice were sacrificed and CD4 ϩ T cells were isolated from spleens. CD11a high CD49d ϩ staining has been shown to delineate previously activated CD4 ϩ T cells from naive cells in Plasmodium-infected mice (4,19) and therefore represent T cells that are likely to respond to a variety of Plasmodium antigens. We compared the responses and phenotypes of the CD4 ϩ CD11a high CD49d ϩ T cell populations from wild-type and Nfat1 Ϫ/Ϫ naive mice with those from mice infected with P. yoelii 17XNL.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if NFAT1 could also play a role in controlling the exhaustion of T cells, we infected wild-type and Nfat1 Ϫ/Ϫ mice with Plasmodium yoelii 17XNL. Infection with this parasite had been previously shown to induce potent exhaustion of CD4 ϩ T cells (4). Following 3 weeks of infection, mice were sacrificed and CD4 ϩ T cells were isolated from spleens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation